2021
DOI: 10.1099/ijsem.0.005120
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium leguminum sp. nov., isolated from nodules of Phaseolus vulgaris in Spain

Abstract: Two endophytic strains, coded MOVP5T and MOPV6, were isolated from nodules of Phaseolus vulgaris plants grown on agricultural soil in Southeastern Spain, and were characterized through a polyphasic taxonomy approach. Their 16S rRNA gene sequences showed 99.3 and 99.4 %, 98.9 and 99.6 %, and 99.0 and 98.7% similarity to ‘ A. deltaense ’ YIC 4121T, A. radiobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The bacteria belonging to these genera are agronomically relevant for their PGP traits, and biocontrol activity is known for their ability to produce plant growth hormones, which can be beneficial for plant growth (Dutkiewicz et al., 2016; Luziatelli et al., 2020). Pseudarthrobacter species have been found in the rhizosphere of various plant species, Medicago sativa rhizosphere in Hail District, Saudi Arabia (Sulieman et al., 2022); nodules of Phaseolus vulgaris L. (Castellano‐Hinojosa et al., 2021); and the rhizosphere and bulk soil of Sulla spinosissima (Oubohssaine et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria belonging to these genera are agronomically relevant for their PGP traits, and biocontrol activity is known for their ability to produce plant growth hormones, which can be beneficial for plant growth (Dutkiewicz et al., 2016; Luziatelli et al., 2020). Pseudarthrobacter species have been found in the rhizosphere of various plant species, Medicago sativa rhizosphere in Hail District, Saudi Arabia (Sulieman et al., 2022); nodules of Phaseolus vulgaris L. (Castellano‐Hinojosa et al., 2021); and the rhizosphere and bulk soil of Sulla spinosissima (Oubohssaine et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we reported the occurrence of Agrobacterium leguminum, Achromobacter denitrificans , Pseudomonas extremorientalis and Serratia quinivorans in the roots of mungbean for the first time. Recently, Castellano-Hinojosa et al (2021) isolated A. leguminum from the Phaseolus vulgaris nodules and claimed it as a novel species based on the data obtained from colony morphology, sequence analysis, phylogenetic analysis and taxonomic characterization. Previously, Sultana et al (2020) isolated A. denitrificans from the rice plant, which showed PGP properties under salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…Agrobacteria are commonly found in soil microflora, with the majority being non-phytopathogenic ( 1 ). Recently, a novel species, Agrobacterium leguminum , was first isolated from the nodules of Phaseolus vulgaris grown in southeastern Spain ( 2 ).…”
Section: Announcementmentioning
confidence: 99%